Penerapan Metode Simple Additive Weigthing Untuk Penentuan Level Kondisi Penyandang Disabilitas - Asminah, Asminah (Building of Informatics, Technology and Science (BITS), 2022)
The Pagar Alam City Service determines the level of condition of persons with disabilities by collecting data in the field, then the results are determined by conclusions and logic based on individual characteristics without any further calculations through predetermined criteria. So that in determining the level of the condition of persons with disabilities, errors often occur with results that are not optimal, such as errors in predicting and determining the condition of persons with disabilities, besides that the data collection process is still recorded in a book and then recapitulated into the Microsoft Excel application so that this method still often accumulates data. This research has the aim of creating a system that is able to determine the level of condition of persons with disabilities by applying the SAW or Simple Additive Weighting calculation method. The results of this study are a decision support system that is able to determine the level of conditions for people with disabilities including people who are blind, deaf, quadriplegic, speech impaired and mentally retarded with mild, moderate and severe conditions using the Simple Additive Weighting (SAW) calculation method.